Estimation of Stature by Percutaneous Measurement of Forearm and Hand (Indian Internet Journal of Forensic Medicine and Toxicology, 2014)
Stature is one of the important criteria for identification. Estimation of stature has special importance when a dead body is found in the mutilated or dismembered state. In present study, attempt is made to reconstruct stature by percutaneous measurement of forearm and hand. A total 180 healthy medical students (90 male and 90 female) of SRG Hospital and Medical College, Jhalawar, Rajasthan were included in study. All students belonged to 18-25 age group. Measurements of stature and left forearm and hand were taken. They were statistically analysed to determine the correlation between stature and length of forearm and hand.
Keywords: Stature; Regression equation; Multiplication factor; Percutaneous measurement,; Forearm and hand